A REVIEW ON PROTEIN TYROSINE PHOSPHATASES - AN IMPORTANT TARGET FOR VARIOUS DISEASES - R, Venkataraghavan; Devi P, Brindha; S, Ivo Romauld (Asian Journal of Pharmaceutical and Clinical Research, 2018)
The enzyme protein tyrosine phosphatase (PTP) is responsible for the regulation of cellular functions including cell growth, replication, and signal transduction. Dysregulation of this enzyme leads to various diseases including Type II diabetes and cancers as well. The PTP enzyme functions as a promising drug target for these diseases, leading to new innovations in developing new drug targets in the field of clinical studies and pharmacology. The PTP is considered as the next generation drug targets. The protein tyrosine drug targets can be targeted to cure the diseases caused due to its dysregulations. However, due to its complex structure and highly conserved active sites are the major challenges which block this strategy. Moreover, two enzyme proteins PTP A and PTP B of PTP enzyme family are essential for the survival of Mycobacterium in host macrophages and cause infection resulting in chronic tuberculosis. The novel drug-like properties of L335-M34 and L01Z08 compounds are selective inhibitors of this enzyme responsible for the tuberculosis virulence in mammals. Some of the commercial inhibitors such as ertiprotafib, arylbenzonaphthofurans, and arylbenzonaphthothiophenes have also proven to inhibit the enzyme's virulence. This review summarizes the latest innovations to lead a map for developing new innovative drugs against the various classes of target enzymes of tyrosine phosphatase.